Warmer nights offer no respite for a defensive mutualism. Issue 8 (27th May 2020) - Higashi, Clesson H. V.; Barton, Brandon T.; Oliver, Kerry M.
Abstract: Ecologically relevant symbioses are widespread in terrestrial arthropods but based on recent findings these specialized interactions are likely to be especially vulnerable to climate warming. Importantly, empirical data and climate models indicate that warming is occurring asynchronously, with night‐time temperatures increasing faster than daytime temperatures. Daytime (DTW) and night‐time warming (NTW) may impact ectothermic animals and their interactions differently as DTW results in greater daily temperature variation and moves organisms nearer to their thermal limits, while NTW avoids thermal limits and may relieve constraints of cooler night‐time temperatures; a nuance that has largely been ignored in the literature. In laboratory experiments, we investigated how the timing of warming influences a widespread defensive mutualism involving the pea aphid Acyrthosiphon pisum, and its heritable symbiont, Hamiltonella defensa, which protects against an important natural enemy, the parasitic wasp Aphidius ervi . Three aphid sublines were experimentally created from single aphid genotype susceptible to A. ervi : one line infected with a highly protective H. defensa strain, one infected with a moderately protective strain and one without any facultative symbiont. We examined aphid fitness in the presence and absence of parasitoids and when exposed to an average 2.5°C increase occurring across three warming scenarios (night‐time vs. daytime vs. uniform) relative to no‐warming controls. An increase of 2.5°C, as predicted to occur by the IPCC before 2100, was sufficient to disable the aphid defensive mutualism regardless of the timing of warming; a surprising result given that the daily maxima for control and NTW scenarios were identical. We also found that warming negatively impacted (a) symbiont‐mediated interactions between host and parasitoid more than symbiont‐free ones; (b) species interactions (host–parasitoid) more than each participant independently and (c) aphids more than parasitoids even though higher trophic levels are generally predicted to be more affected by warming. Here we show that 2.5°C warming, regardless of timing, negatively impacted a common microbe‐mediated defensive mutualism. While this was a laboratory‐based study, results suggest that temperature increases predicted in the near‐term may disrupt the many ecological symbioses present in terrestrial ecosystems. Abstract : This study examines how the timing of warming effects species interactions, and the first to do in an arthropod symbiosis. Most arthropod species are infected with heritable symbionts, many of which are of medical, veterinary and agricultural importance and therefore understanding how global climate change will impact these is critical.